2020
DOI: 10.5829/ije.2020.33.04a.14
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Properties of Metakaolin-based (Na, K)-Geopolymer Using Taguchi Design Method

Abstract: Geopolymer paste is an innovative construction material which shall be produced by chemical action of inorganic molecules. It is a more environmentally friendly alternative to conventional Portland cement which is abundantly available worldwide. In this study, the influence of different alkaline activators (Na and K) on the mechanical and thermal behaviors of metakaolin-based geopolymer was investigated. The aims of this study is to find out the mixes and their process parameters, which are appropriate to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Metakaolin is widely used in mortar and concrete as pozzolanic material; it has a significant impact on improving the mechanical and durability properties of mortar and concrete [23][24][25][26]. Because of its highly amorphous structure, is known as the most reactive material for the geopolymerization process.…”
Section: Figure 1 Characteristic Of Pcm Materialsmentioning
confidence: 99%
“…Metakaolin is widely used in mortar and concrete as pozzolanic material; it has a significant impact on improving the mechanical and durability properties of mortar and concrete [23][24][25][26]. Because of its highly amorphous structure, is known as the most reactive material for the geopolymerization process.…”
Section: Figure 1 Characteristic Of Pcm Materialsmentioning
confidence: 99%
“…It is well known that the pores inside the material reduces the mechanical strength of the geopolymer [25,26]. On the other hand, in the many applications were desired to have a material that combines high porosity and high mechanical strength.…”
Section: H2o2 → H2o + ½ O2mentioning
confidence: 99%
“…Usually it can only consider single quality characteristics. While, Grey Relational Analysis (GRA) is usually employed to deal with the multi-quality characteristics [26]. This is because, GRA is a normalization evaluation technique to solve a complicated multi-performance characteristics optimization effectively [27].…”
Section: H2o2 → H2o + ½ O2mentioning
confidence: 99%
“…This value seemed to be reasonable because the value of R + cations provide the positive charge that stabilizes the negative charge came from Al 3+ in tetrahedral sites, leading to geopolymer formation [9,10]. The effect of mixed alkali geopolymer on compressive strength instead of one type pure alkaline was studied by researchers like Duxson et al (2007) who observed that the use of mixed alkali of Na and K in geopolymer synthesis with Si/Al≥1.90 can increase the compressive strengths compared with geopolymer specimens contain Na or K, the later specimens decrease strength notably [11,12]. The compressive strength of geopolymer is time dependent property due to it increased with time increased [12].…”
Section: Introductionmentioning
confidence: 99%